Vitamin D3 favorable outcome on recognition memory and prefrontal cortex expression of choline acetyltransferase and acetylcholinesterase in experimental model of chronic high-fat feeding. (3rd March 2020) - Alrefaie, Zienab; Moustafa, Injy
Abstract: Aim of the study: High-fat diet (HFD) consumption and insufficient vitamin D levels are globally increasing phenomena. The present study assessed the effect of chronic HFD feeding with and without vitamin D supplementation on recognition memory and prefrontal cortex expression of choline acetyltransferase (CAT) and acetylcholinesterase (Achase). Materials and methods: Forty male Wistar rats were subjected to four dietary regimens ( n = 10); control diet (10% fat), control + vitamin D3, high-fat diet (HFD 45% fat) and HFD + vitamin D3 for 6 months. Rats were tested for the novel object recognition test, and their prefrontal cortices were assessed for expression of CAT and Achase. Results: Recognition memory was impaired in HFD-fed rats compared to control rats as evidenced by significantly decreased discrimination index in the novel object recognition test. Moreover, CAT expression was significantly decreased while Achase expression was significantly increased in the prefrontal cortex of HFD-fed rats. Vitamin D3 supplementation with HFD significantly increased the exploration of the novel object and the discrimination index and attenuated the alterations in the prefrontal cortex CAT and Achase expression. Conclusions: The present findings support the potential effect of vitamin D on recognition memory and cholinergic transmission in the prefrontal cortex and add to the pathophysiology of HFD consumption.